Cyber Indoctrination Victims in Indonesia and Uzbekistan: Victim Protection and Indoctrination in Practice - Budiono, Arief; Absori, Absori; Wardiono, Kelik; Yuspin, Wardah; Gulyamov, Said Saidakhrarovich (Journal of Human Rights, Culture and Legal System, 2023)
Terrorism has become a global phenomenon, affecting not only those hurt or killed by acts of terrorism but also involving women as significant contributors to indoctrination worldwide, including in Indonesia and Uzbekistan. This research aims to explain the evolving roles of women in terrorism in Indonesia and Uzbekistan and how terrorists use cyber indoctrination to target women in these countries. The research was conducted in Indonesia and Uzbekistan using the classical-normative dogmatic juridical method with a library-based approach. Cyber indoctrination has proven highly effective in persuading women to join and take initiative in acts of terror. Women who become involved in terrorism due to exposure to pseudo-religious ideologies through cyber indoctrination have human rights and should be legally protected as victims of cyber indoctrination by terror groups. This article contributes to the recognition of women's rights as victims of cyber indoctrination and sheds light on the changing role of women in terrorism. It aims to raise awareness among society, governments, law enforcement agencies, and religious leaders about the strategies of pseudo-religious cyber indoctrination employed by terrorists. It encourages them to take preventive and repressive actions to combat terrorism and safeguard women from its allure.